2-Nonanol produced by Bacillus velezensis EM-1: a new biocontrol agent against tobacco brown spot - Sui, Xiaona; Han, Xiaobin; Wang, Xianbo; Wan, Jun; Wen, Mingxia; Zhao, Donglin; Zheng, Yanfen; Zhang, Chengsheng; Xu, Chuantao; Wang, Youqiang (Frontiers in Microbiology, 2025)
Tobacco brown spot disease, caused by Alternaria alternata, poses a significant threat to crop production. Traditional control methods, particularly chemical fungicides, have raised concerns about environmental impact and resistance. Although our previous research has shown that volatile compounds produced by Bacillus velezensis EM-1 can effectively suppress A. alternata, the specific antifungal compounds and their mechanisms remain unclear. In this study, exposure to the volatiles from strain EM-1 significantly inhibited the mycelial growth and spore germination of A. alternata, with 2-nonanol identified as the most potent antifungal compound. Fumigation experiments revealed that 2-nonanol exhibited strong dose-dependent toxicity, with an EC50 of 0.1055 μL/cm3 and a minimum inhibitory concentration of 0.2166 μL/cm3. In vivo experiments on tobacco leaves confirmed that 2-nonanol effectively reduced tobacco brown spot disease incidence and slowed lesion expansion. Transcriptome analysis indicated that 2-nonanol downregulated the expression of genes encoding D-glucose synthesis in carbon metabolism, which limited energy acquisition by A. alternata. Moreover, the expression of antioxidant enzymes, including superoxide dismutase (SOD) and catalase (CAT), was markedly suppressed by 2-nonanol, thereby exacerbating cellular damage induced by oxidative stress. These findings suggest that 2-nonanol holds potential as a biocontrol agent for managing tobacco brown spot disease, underscoring the promising role of volatile organic compounds (VOCs) in the development of environmentally friendly biocontrol products.